A study of specific immunoglobulin G4 expression in allergic rhinitis and its value in assessing efficacy and in predicting prognosis of sublingual immunotherapy - Ting‐Ting Wei; Kai Gao; Jun‐Hu Tai; Yong‐Jun Wei; Bin Zhan (Kaohsiung Journal of Medical Sciences)
Abstract Allergic rhinitis (AR) is a widespread health issue with a rising global prevalence, and sublingual immunotherapy (SLIT) has shown efficacy in AR treatment. We examined specific immunoglobulin G4 (sIgG4) expression in AR and its role in evaluating SLIT efficacy and predicting patient prognosis. We compared total nasal symptom score (TNSS), total medication score (TMS), visual analogue scale (VAS) score, inflammatory cytokines, and immune function markers in AR patients before and after SLIT. SLIT reduced TNSS, TMS, VAS scores, IL‐4, IL‐17, eosinophilia percentage (EOS%), and specific immunoglobulin E (sIgE) levels, while increasing INF‐γ, IL‐10, and sIgG4. The sIgG4 level at pre‐treatment and 12 months post‐treatment was negatively correlated with TNSS, TMS, VAS score, IL‐4, IL‐17, EOS%, and sIgE, and positively correlated with IFN‐γ and IL‐10. Most patients showed symptomatic improvement. After 12 months, sIgG4 level demonstrated an area under the curve (AUC) of 0.867 for assessing SLIT as effective. Pre‐treatment sIgG4 level showed an AUC of 0.869 for predicting SLIT as effective. Collectively, sIgG4 has strong potential assessing SLIT efficacy and prognosis in AR patients, with correlations to TNSS, TMS, VAS score, and IL‐4, IL‐10, IL‐17, INF‐γ, EOS% and sIgE levels.